Assessing upper limb function in multiple sclerosis. (June 2014) - Lamers, Ilse; Feys, Peter
The need to fully assess upper limb function in multiple sclerosis (MS) has become increasingly clear with recent studies revealing a high prevalence of upper limb dysfunction in persons with MS leading to increased dependency and reduced quality of life. It is important that clinicians and researchers use tailored outcome measures to systematically describe upper limb (dys)function and evaluate potential deterioration or improvement on treatment. This topical review provides a comprehensive summary of currently used upper limb outcome measures in MS, classified according to the levels of the International Classification of Functioning (ICF). The clinical utility, strengths, weaknesses and psychometric properties of common upper limb outcome measures are discussed. Based on this information, recommendations for selecting appropriate upper limb outcome measures are given. The current shortcomings in assessment which need to be addressed are identified.